Modulus-switching viscoelasticity of electrorheological networks - Chin, Byung D.; Chun, Myung-Suk; Winter, H. Henning (SPRINGER, 2009)
To form an electrorheological network (ERN), semiconducting nanoparticles were embedded in a polymer that was cross-linked to restrict particle motion. The microstructure ranged from random to aligned, depending on the degree of field-induced particle alignment during chemical network formation. We investigated in detail the softness effects of the matrix, having a relatively low storage modulus, on the dynamic rheological behavior of the ERN and analyzed its anisotropy. The anisotropy of the microstructure was probed rheologically with the modes of small-amplitude oscillatory shear (loading perpendicular to the field direction) and compression (loading in the field direction). The storage shear modulus was found to be a function of the applied electric field, particle volume fraction, and the pre-alignment electric field strength during the cross-linking reaction of the matrix, which governs the thickness of particle columns and intercolumn distance. Nonlinear behavior at small strain (below 0.1%) was conspicuous; this nonlinear viscoelasticity was accompanied by only a limited deformation of ordered connectivity. Throughout this study, we fabricated the ERN with the highly controllable modulus-switching effect acting in a shear-mode operation. Managing this anisotropy of an ERN by the electrical and chemical process is important in the design of smart materials that will provide improved stability and mechanical strength compared with fluid-type electrorheological materials and faster response time compared with that of conventional charged polymer gel.
Keywords: YIELD-STRESS; GEL; DISPERSIONS; SUSPENSIONS; COMPOSITES; PARTICLES